2021
DOI: 10.1002/alz.12238
|View full text |Cite
|
Sign up to set email alerts
|

Brain structures and networks responsible for stimulation‐induced memory flashbacks during forniceal deep brain stimulation for Alzheimer's disease

Abstract: Introduction Fornix deep brain stimulation (fx‐DBS) is under investigation for treatment of Alzheimer's disease (AD). We investigated the anatomic correlates of flashback phenomena that were reported previously during acute diencephalic stimulation. Methods Thirty‐nine patients with mild AD who took part in a prior fx‐DBS trial (NCT01608061) were studied. After localizing patients’ implanted electrodes and modeling the volume of tissue activated (VTA) by DBS during systematic stimulation testing, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…Additionally, as no native resting state functional MRI data were available, the functional connectivity analysis was performed using high-resolution and high-fidelity normative data from healthy individuals. Although normative data may not fully represent patient or pathology-specific functional connectivity, it has been shown to yield similar results to patient-specific data in prior analyses [7,12].…”
Section: Brain Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, as no native resting state functional MRI data were available, the functional connectivity analysis was performed using high-resolution and high-fidelity normative data from healthy individuals. Although normative data may not fully represent patient or pathology-specific functional connectivity, it has been shown to yield similar results to patient-specific data in prior analyses [7,12].…”
Section: Brain Stimulationmentioning
confidence: 99%
“…Retrospective imaging analysis was performed to elucidate the neurocircuitry underlying response to stimulation. This involved DBS electrode localization (https://www.lead-dbs.org/), volume of activated tissue (VAT) modelling, and mapping of areas functionally connected to the VATs using a normative connectome [7] (see supplementary materials for detailed description).…”
mentioning
confidence: 99%
“…The connectome is key for understanding how the brain works. Over the last years, multiple studies have demonstrated that neurological and psychiatric symptoms can be mapped to a common distributed brain network [19][20][21][22][23][24][25][26][27][28][29][30]. The brain connectome can be assessed using different MRI acquisitions: (1) diffusion-weighted MRI (dMRI) to estimate the structural connectivity using the directionality of water diffusion to evaluate tracts and projections [31]; (2) resting state functional MRI (rsfMRI) to estimate functional connectivity making use of the lowfrequency blood oxygen level-dependent (BOLD) fluctuations found in brain regions that are functionally related to each other [32].…”
Section: Connectomicsmentioning
confidence: 99%
“…Using the segmented feature in the template space as the input in the normative functional and structural connectomes, one can then identify the brain-wide network of functionally and structurally connected areas (Figure 2). This allows identification of networks involved in clinical symptoms or disease processes (Figure 1) [22,[25][26][27]46]. For Using the segmented feature in the template space as the input in the normative functional and structural connectomes, one can then identify the brain-wide network of functionally and structurally connected areas (Figure 2).…”
Section: Practical Framework For Normative Brain Analysesmentioning
confidence: 99%
“…Recognizing these remote effects of DBS, one can also conceptualize that connectomic analysis may provide insight into the underlying basis of adverse effects or undesirable symptoms occurring secondary to DBS. Such an approach has been used to map the underlying connectivity of DBS-associated flashback phenomena following forniceal DBS, panic attacks induced by inferior thalamic peduncle DBS, and seizures following subcallosal cingulate DBS for refractory anorexia nervosa [ 30 , 31 , 32 ]. Similarly, connectivity-derived models can guide effective DBS for less well-understood pathologies, such as central post-stroke pain and neuropsychiatric indications, including obsessive-compulsive disorder [ 8 , 33 ].…”
Section: Integrating Connectomic Analysis Into the Glioma Peri-operative Pipeline: Lessons From Functional Neurosurgerymentioning
confidence: 99%